A Computational Fluid Dynamics Simulation Method to Optimize the Structure Parameters of Coal‐Based Flash Ironmaking Reactors. Issue 4 (27th October 2021) - Yang, Yiru; Guo, Lei; Guo, Zhancheng
Abstract : The coal‐based flash ironmaking furnace is designed to industrialize the novel flash ironmaking technology (FIT), which is recognized as a cleaner and efficient alternative ironmaking process. To realize gas‐particle contact, researchers use the cocurrent downer to reduce bonding, and the reactor structure has a significant effect on the flow pattern. Herein, a 3D computational fluid dynamics (CFD) model is developed to obtain an in‐depth understanding of the geometry parameters, including ore feeding position ( r / R ), shaft diameter ( D ), and height‐to‐diameter ratio ( L / D ). The simulation results show that the secondary gas flow caused by the dropping hematite particles might enhance or destroy the primary turbulence structure when r / R was below or above 0.6. The increased shaft diameter D expanded the recirculation zone, which helps to prolong the residence time and improve the species exchange. The particles' reduction degrees first rise and then fell, and the highest value (90.89%) is attained at D  = 2.2 m. On the contrary, the increased L / D ratio does not change the turbulence structure but prolongs the length of the plug zone. It also shows a positive but declining effect on the reduction degree from 89.7% to 99.8%. Abstract : The coal‐based flash ironmaking furnace is redesigned by computational fluid dynamics (CFD) method to industrialize cleaner flash ironmaking technology (FIT). An in‐depth understanding of the geometry parameters is obtained, including ore feeding position, shaft diameter, and height‐to‐diameter ratio. The simulation results predicate the new founding in the coupling process, such as secondary gas flow caused by ore feeding.